The Analysis of the contextual meaning Expression of the word ‘Cry’ from the Children’s book written by Enid Blyton - Paulina Novarita; Wahyu Satya Gumelar; Syifa Sonia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze the contextual meaning of the word "cry" found in the texts of children's books by Enid Blyton and to explore how this word is translated into Indonesian. Using a qualitative descriptive approach, this research employs semantic analysis to understand the variations in meaning and emotional nuances contained in the use of the word "cry" across different narrative contexts. The qualitative semantic method allows the researcher to delve into the meanings of words within social and cultural contexts, as well as how these meanings can shift depending on the situation and the emotions of the characters. Data were collected from four purposively selected stories, and analysis was conducted on ten sentences containing the word "cry." The findings reveal that "cry" is a polysemous word that conveys a range of meanings, including expressions of joy, fear, and mockery, all of which are influenced by the narrative context. This study emphasizes the importance of understanding contextual meaning in literary analysis and translation, as well as the challenges faced in preserving emotional nuances when translating polysemous words.